High Lipid Content of Prey Fish and n−3 PUFA Peroxidation Impair the Thiamine Status of Feeding-Migrating Atlantic Salmon (Salmo salar) and Is Reflected in Hepatic Biochemical Indices - Marja Keinänen; Soili Nikonen; Reijo Käkelä; Tiina Ritvanen; Mervi Rokka; Timo Myllylä; Jukka Pönni; Pekka J. Vuorinen (Biomolecules, 2022)
Signs of impaired thiamine (vitamin B1) status in feeding-migrating Atlantic salmon (Salmo salar) were studied in three Baltic Sea areas, which differ in the proportion and nutritional composition of prey fish sprat (Sprattus sprattus) and herring (Clupea harengus). The concentration of n−3 polyunsaturated fatty acids (n−3 PUFAs) increased in salmon with dietary lipids and n−3 PUFAs, and the hepatic peroxidation product malondialdehyde (MDA) concentration increased exponentially with increasing n−3 PUFA and docosahexaenoic acid (DHA, 22:6n−3) concentration, whereas hepatic total thiamine concentration, a sensitive indicator of thiamine status, decreased with the increase in both body lipid and n−3 PUFA or DHA concentration. The hepatic glucose 6-phosphate dehydrogenase activity was suppressed by high dietary lipids. In salmon muscle and in prey fish, the proportion of thiamine pyrophosphate increased, and that of free thiamine decreased, with increasing body lipid content or PUFAs, or merely DHA. The thiamine status of salmon was impaired mainly due to the peroxidation of n−3 PUFAs, whereas lipids as a source of metabolic energy had less effect. Organochlorines or general oxidative stress did not affect the thiamine status. The amount of lipids, and, specifically, their long-chain n−3 PUFAs, are thus responsible for generating thiamine deficiency, and not a prey fish species per se.